Green core clinopyroxenes from Martin Vaz Archipelago Plio-Pleistocenic alkaline rocks, South Atlantic Ocean, Brazil: A magma mixing and polybaric crystallization record. (January 2021) - Leite de Oliveira, André; Costa dos Santos, Anderson; Nogueira, Camila Cardoso; Maia, Thaís Mothé; Geraldes, Mauro César
Abstract: Martin Vaz Archipelago is located at the parallel 20°S, 1200 km away from the Brazilian coastline and is composed of Plio-Pleistocenic alkaline rocks that represent the last volcanic event of the Vitória-Trindade Ridge. The Archipelago is divided into three main units: Pico das Gaivotas Unit (i) is made up of nosean-phonolite and phono-tephrite domes and tephri-phonolite dykes with clinopyroxene, nosean and potassic feldspar phenocrysts, and scarce kaersutite anhedral phenocrysts; the Bandeira Unit (ii), in turn, comprises melanephelinitic and basanitic lava flows with olivine and clinopyroxene (diopside) phenocrysts; and lastly, the Basal Unit (iii) is composed of pyroclastic deposits with tuffs, lapilli-tuffs and lapillite. The clinopyroxene phenocrysts from Pico das Gaivotas and Bandeira Units have anhedral green cores with sieved and poikilitic textures and show reaction rims composed of opaque minerals, indicating disequilibrium and compositional changes in the liquid. This study provides mineral chemistry data indicating that clinopyroxene rims are more primitive (Mg# 57.46–84.12) and enriched in Al–Ti–Fe 3+ -Ca compared to the Fe-rich green-cores, probably related with a more primitive Ca-rich magma input in the magmatic chamber after the green-core crystallization from a different liquid. Olivine crystals from Bandeira Unit show resorption features and no compositional affinity with the analyzed liquid, indicating that these crystals have a xenocrystic origin from mantle peridotitic source. Clinopyroxene geothermobarometry data suggest different pressure and temperature conditions for cores and rims during crystallization, reflecting a polybaric evolutionary history. Pico das Gaivotas Unit clinopyroxene phenocrysts suggest a particularly higher-pressure environment, and a complex evolutionary history. Highlights: Green-core cpx thermodynamics and petrographic features. Magma replenishing at Martin Vaz volcanic system Olivine xenocrysts related to hybrid origin. Polybaric evolutionary history.